2016
DOI: 10.18632/oncotarget.9934
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of Krüppel-like factor-4 by microRNA-135a-5p promotes proliferation and metastasis in hepatocellular carcinoma by transforming growth factor-β1

Abstract: Krüppel-like Factor-4 (KLF4) is a zinc finger transcription factor which plays an important role in cell cycle, proliferation and apoptosis. In Hepatocellular Carcinoma (HCC), the function of KLF4 has been characterized as tumor suppressor. However, the mechanism remains largely unknown. In this study, we demonstrated that TGF-β1 down-regulated KLF4 by activating miR-135a-5p. MiR-135a-5p promoted proliferation and metastasis in HCC cells by direct targeting KLF4 both in vitro and in vivo. In addition, miR-135a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 43 publications
(44 reference statements)
1
35
0
1
Order By: Relevance
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…Many miRNAs identified as dysregulated in the present study have also been reported as altered in other cancer types, including breast cancer (miR‐374b‐5p, miR‐429, miR‐200b‐5p, miR‐200b‐3p, miR‐187‐3p, miR‐196a‐5p, miR‐183‐5p, miR‐21‐5p, and miR‐182‐5p); gastric cancer (miR‐374b‐5p, miR‐200c‐3p, miR‐18b‐5p, miR‐196a‐5p, miR‐21‐5p, and miR‐20a‐3p); ovarian cancer (miR‐141‐5p, miR‐182‐5p, miR‐483‐3p, and miR‐200c‐3p); hepatocellular carcinoma (miR‐135a‐5p, miR‐187‐3p, miR‐148a‐5p, miR‐200a‐3p, and miR‐9‐3p); colorectal cancer (miR‐9‐3p, miR‐135a‐5p, miR‐200c‐3p, miR‐200b‐3p, and miR‐182‐5p); thyroid cancer (miR‐7‐5p and miR‐9‐3p); lung cancer (miR‐200b‐5p, miR‐200b‐3p, miR‐9‐5p, miR‐200a‐3p, and miR‐21‐5p); pancreatic cancer (miR‐200b‐3p, miR‐483‐3p, and miR‐183‐5p); chronic lymphocytic leukemia (miR‐4521, miR‐7‐5p, and miR‐182‐5p); Hodgkin lymphoma (miR‐876‐5p); cervical cancer (miR‐429); head and neck squamous cell carcinoma (miR‐200b‐5p); and bladder cancer (miR‐148a‐3p) …”
Section: Discussionsupporting
confidence: 65%
“…High miR-135a levels favour invasive and metastatic growth of HCC cells in vitro and are correlated with malignant portal vein thrombosis, possibly by directly targeting MTSS1 [20]. Other targets of miR-135a investigated in vitro are forkhead box O1, matrix metalloproteinase-2, AKT pathway, and Krüppel-like factor-4 [21, 22]. Therefore, from a functional perspective, elevated levels of miR-135a might induce early formation of microscopic HCC dissemination via several pathways, and thus, result in early HCC recurrence after curative resection.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Liu et al showed that overexpression of miR-135a favours an invasive and metastatic behaviour of HCC in vitro and is associated with malignant portal vein thrombosis in vivo, most likely by directly targeting metastasis suppressor 1 (MTSS1) [20]. Two other studies showed that miR-135a also down-regulates Krüppel-like factor 4, up-regulates the expression of matrix metalloproteinase-2 and Akt, and down-regulates forkhead box O1, resulting in higher proliferation and invasiveness of HCC cells [21, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…It blocks HCC progression by reducing expression of SLUG, TIMP1 , and TIMP2 and by inducing expression of vitamin D receptor and hepatocyte nuclear factor-6 (HNF6) 232, 234-236 . Levels of KLF4 are reduced in cancer cells by miRNAs and increased protein degradation 237, 238 .…”
Section: Roles In the Digestive System And Diseasesmentioning
confidence: 99%